The Attractivity of Ornamental Plants to Some Natural Enemies of Pest - Fatima Ramdan Muhamed Al Kawan; Bagyo Yanuwiadi; Zaenal Fanani (Indonesian Journal of Environment and Sustainable Development, 2018)
There are several roles of ornamental plants to environment management and human being. One of them is to attract some natural enemies of pest which more ecofriendly and specific target. Related with this role, the objectives of this study are to inventory kind of ornamental plants in the play ground, to inventory kind of ornamental plants which attract natural enemies, and to know the foreign students perception to the function of the ornamental plant species for attracting the natural enemies. This study was conducted using Visual Encounter Survey (VES) method with three repetitions. The result showed that there were 5 ornamental plants in the area study as Acalypha siamensis, Osmoxylon lineare, Canna indica, Crinum asiaticum L. and Oleina syzigium. Data analysis using Community structure of Arthropods, Index of Diversity, and Index of Similarity on different area. The result Based on the average of species abundance, O. lineare is the most visited plant by animals. It was showed from range of average of species abundance which reached from 0.17 to 13.72 individu. The second one was A. siamensis which had average of species abundance 0.14 - 13.14 individu. The next plant which visited by many animals are C. indica and C. asiaticum L. The average of species abundance respectively varied from 0.43 to 12.00 individu and from 0.14 to 8.72 individu. Oleina syzigium became the least one, because the average of species abundance reached from 0.14 to 3.14 individu. Overall, the level of respondents (foreign students) knowledge about the function of ornamental plants for attracting natural enemies was categorized into highKey words: Attractivity, Natural enemies, Ornamental plants